THEORETICAL AND PRACTICAL PRINCIPLES OF SOCIAL SPHERE SPECIALISTS TRAINING IN INTERPROFESSIONAL INTERACTION - Yana Raievska (International Journal of Innovative Technologies in Social Science, 2021)
The article considers aspects of professional development of social sphere specialists; professional roles, functions and content of professional activity are described; the leading principles of organizational and methodological assistance of the social specialists training process are determined. The development of interprofessional interaction ideas is connected with the interprofessional group characteristics, professional and external image, competency areas, activity range and different status in the social work system. The concept of dialogic-competence approach forms the basic principles of interprofessional interaction: system, comprehensiveness, relevance, consistency, mutual enrichment, prospects, and self-efficacy. Interprofessional interaction involves mutual acceptance, dialogic orientation of specialists, psychological equality between all participants, the availability and sufficiency of space to build a workflow, compliance with the rules, ensuring a friendly atmosphere in joint activities. Development of readiness for interprofessional interaction includes communicative (efficiency of interpersonal and intrapersonal communications), cooperative (productive partnership in joint activity), personal-reflexive (analysis of own mental states, own actions; ability to allocate, analyze and compare own actions with the subject situation), social, team, system, mediation competences. Mechanisms for interprofessional interaction are cooperation, communication, coordination, specialists’ consistency actions, emotional, cognitive-analytical, regulatory functions of the individual. The development of psychological readiness components for interprofessional interaction among respondents is expressed at the average level with a general tendency among Master students with motivational and emotional component and among specialists with activity-practical component to a high-level indicators and a general tendency among Bachelor students with cognitive-semantic, actively practical and regulatory components to a low-level indicators.